2008
DOI: 10.1111/j.1398-9995.2008.01716.x
|View full text |Cite|
|
Sign up to set email alerts
|

A case‐control study of the relation between plasma selenium and asthma in European populations: a GA2LEN project*

Abstract: This study does not support a role for selenium in protection against asthma, but effect modification and confounding cannot be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
3
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 171 publications
(193 reference statements)
3
51
3
4
Order By: Relevance
“…For example, a number of epidemiological studies have reported that asthma incidence, prevalence, or severity is associated with reduced Se status (52,69,92,120,130,170,190,202,228,244). This is in contrast to findings in a large, multi-regional study conducted under the Global Allergy and Asthma European Network, in which asthma prevalence/severity data from 14 centers in Europe showed no significant association between Se status and asthma levels (33). Other studies also have failed to confirm a link between Se levels or GPx activities and development of asthma.…”
Section: Intestinal Inflammation and Food-borne Illnessescontrasting
confidence: 55%
“…For example, a number of epidemiological studies have reported that asthma incidence, prevalence, or severity is associated with reduced Se status (52,69,92,120,130,170,190,202,228,244). This is in contrast to findings in a large, multi-regional study conducted under the Global Allergy and Asthma European Network, in which asthma prevalence/severity data from 14 centers in Europe showed no significant association between Se status and asthma levels (33). Other studies also have failed to confirm a link between Se levels or GPx activities and development of asthma.…”
Section: Intestinal Inflammation and Food-borne Illnessescontrasting
confidence: 55%
“…Patterns similar to this have often been labelled 'western' and are likely to represent a mixture of dietary components which may independently contribute to asthma risk (5,6) . Heterogeneity in multi-centre studies can also suggest alternative explanations for apparent effects of diet observed in single centres, such as uncontrolled confounding, and would make us cautious of progressing to a trial (36) . Our study was cross-sectional, and a further possibility is reverse causation, people with asthma may alter their diet in a systematic way at a given centre, for example, to be more 'healthy'.…”
Section: Discussionmentioning
confidence: 99%
“…While others studies have found no relationship between serum selenium level and asthma in Japanese and Europe populations [247,248]. Selenium supplementation studies in mouse OVA-induced asthma models have shown that selenium has some protective effects on asthma-associated inflammation.…”
Section: Seleniummentioning
confidence: 96%
“…It contains the active compounds including glycyrrhizin, glycyrrhetinic acid, flavonoids, isoflavonoids, and chalcones [248]. Glycyrrhizin and glycyrrhetinic acid are considered to be the main active components [249] and are potent inhibitors of cortisol metabolism, due to their steroid like structures inhibiting the key steroid metabolic enzymes, delta 4-5-reductase, 11 beta-hydroxysteroid dehydrogenase and 20-hydroxysteroid dehydrogenase [250,251].…”
Section: Licorice Root (Glycyrrhiza Glabra)mentioning
confidence: 99%